2013
DOI: 10.1615/critrevbiomedeng.2013006378
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Lysis: Dynamics Revisited and Advances in On-chip Operation

Abstract: Electrical lysis (EL) is the process of breaking the cell membrane to expose the internal contents under an applied high electric field. Lysis is an important phenomenon for cellular analysis, medical treatment, and biofouling control. This paper aims to review, summarize, and analyze recent advancements on EL. Major databases including PubMed, Ei Engineering Village, IEEE Xplore, and Scholars Portal were searched using relevant keywords. More than 50 articles published in English since 1997 are cited in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…The applied voltage used in the erythrocyte counting experiments is up to 10 V. The electrolysis of the cells depends on many factors including applied voltage and whether it is DC or AC, the frequency of the applied voltage, flow rate of the cells and the critical time for irreversible electroporation 2527 . If the actual transmembrane voltage increases well above 1 V, then electroporation can begin to happen 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The applied voltage used in the erythrocyte counting experiments is up to 10 V. The electrolysis of the cells depends on many factors including applied voltage and whether it is DC or AC, the frequency of the applied voltage, flow rate of the cells and the critical time for irreversible electroporation 2527 . If the actual transmembrane voltage increases well above 1 V, then electroporation can begin to happen 25 .…”
Section: Discussionmentioning
confidence: 99%
“…If the actual transmembrane voltage increases well above 1 V, then electroporation can begin to happen 25 . In our experimental conditions, with 10-V peak voltage at frequency of 303 kHz, and using intracellular resistivity reported in literature, the resulting transmembrane potential can be calculated to be around 2 V. So looking at transmembrane potential only, we would be above the critical voltage to cause cell lysing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the electric eld parameters are well above REP; the nano-pores will not be resealed aer the removal of electric eld, this process is known as irreversible electroporation (IRE) 6,7 which deforms the cell permanently leads to cell lysis/death. 8,9 The external electric eld induces change in voltage/potential across the cell membrane which is termed as induced transmembrane voltage/ potential (ITV). 10,11 The electroporation effect becomes prominent and detectable only when the ITV exceeds the critical or threshold value.…”
Section: Introductionmentioning
confidence: 99%
“…30 In order for a low-voltage power supply (500 V max voltage) to be utilized, the geometry of the internal channel was augmented in areas so that an electric field greater than 1000 V cm −1 could be generated. Wang et al and Lee et al have shown that, for a channel with uniform depth but varying width, a higher electric field can be generated in a narrow region, and the electric fields in the wide and narrow regions can be calculated with the following equations: 2,7 Ew=voltage2Sw+Snfalse(Dw/Dnfalse) En=voltage2Swfalse(Dn/Dwfalse)+Snwhere trueE represents the electric field in the wide (w) or narrow (n) region, S is the segment length, D is the diameter of the channel, and voltage is the applied potential.…”
Section: Resultsmentioning
confidence: 99%